# Simple way to calculate the inverses of these functions [closed]

if we have the following functions:

$f(x)=x^3+x$

$g(x)=x^3+x-9$

$h(x)=x|x|+1$

is there a simple way to calculate these inverses:

$f^{-1}(2)$

$g^{-1}(1)$

$h^{-1}(3)$

## closed as off-topic by CY Aries, GNUSupporter 8964民主女神 地下教會, Namaste, Ethan Bolker, Jose Arnaldo Bebita-DrisMar 31 '18 at 12:40

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – CY Aries, GNUSupporter 8964民主女神 地下教會, Namaste, Ethan Bolker, Jose Arnaldo Bebita-Dris
If this question can be reworded to fit the rules in the help center, please edit the question.

• What do you mean by simple? Solving $x^3+x=x(x^2+1)=2$ should be quite doable isn't it? (In particular if you note that $1^2 = 1$). – Surb Mar 31 '18 at 8:54

Note that since $f(x)=x^3+x$ is injective since $f'(x)=x^2+1>0$

• $f(x)=x^3+x=2\implies x=1 \implies f^{-1}(2)=1$

and also for $g(x)=x^3+x-9$ injective since $g'(x)=x^2+1>0$

• $g(x)=x^3+x-9=1\implies x=2 \implies g^{-1}(1)=2$

and also for $h(x)=x|x|+1$ injective (can you say why?) we can find

• $h(x)=x|x|+1=3\implies x=\sqrt 2 \implies h^{-1}(3)=\sqrt2$
• thank you, this is what i did i just wanted to make sure if it's correct or not – SiN Mar 31 '18 at 9:15
• @SiN You are welcome. For next times show also your effort and work in the OP in order to better help you with your doubts and also to avoid downvoting for a poor format. Bye – gimusi Mar 31 '18 at 9:17
• @SiN The key point here is injectivity,once you show that the functions are injective you are sure that the solution we can find by inspection in unique and then we can find the values for the inverses. – gimusi Mar 31 '18 at 9:19

For $$h(x)=x|x|+1$$ it is not hard to find the inverse function, we only need $h^{-1}(x)$ for $x\geq 0$, so we have $$h^{-1}(x)=\sqrt{x-1}$$